American Association for the Study of Liver Diseases Expert Panel Consensus Statement: Vaccines to Prevent Coronavirus Disease 2019 Infection in Patients With Liver Disease. Issue 2 (26th August 2021) - Fix, Oren K.; Blumberg, Emily A.; Chang, Kyong‐Mi; Chu, Jaime; Chung, Raymond T.; Goacher, Elizabeth K.; Hameed, Bilal; Kaul, Daniel R.; Kulik, Laura M.; Kwok, Ryan M.; McGuire, Brendan M.; Mulligan, David C.; et al.
Abstract : The aim of this document is to provide a concise scientific review of the currently available COVID‐19 vaccines and those in development, including mRNA, adenoviral vectors, and recombinant protein approaches. The anticipated use of COVID‐19 vaccines in patients with chronic liver disease (CLD) and liver transplant (LT) recipients is reviewed and practical guidance is provided for health care providers involved in the care of patients with liver disease and LT about vaccine prioritization and administration. The Pfizer and Moderna mRNA COVID‐19 vaccines are associated with a 94%‐95% vaccine efficacy compared to placebo against COVID‐19. Local site reactions of pain and tenderness were reported in 70%‐90% of clinical trial participants, and systemic reactions of fever and fatigue were reported in 40%‐70% of participants, but these reactions were generally mild and self‐limited and occurred more frequently in younger persons. Severe hypersensitivity reactions related to the mRNA COVID‐19 vaccines are rare and more commonly observed in women and persons with a history of previous drug reactions for unclear reasons. Because patients with advanced liver disease and immunosuppressed patients were excluded from the vaccine licensing trials, additional data regarding the safety and efficacy of COVID‐19 vaccines are eagerly awaited in these and other subgroups. Remarkably safe and highly effective mRNA COVID‐19 vaccines are now available for widespread use and should be given to all adult patients with CLD and LT recipients. The online companion document located at https://www.aasld.org/about‐aasld/covid‐19‐resources will be updated as additional data become available regarding the safety and efficacy of other COVID‐19 vaccines in development.